Evaluasi Sistem Drainase di Pasar Bancong Kelurahan Sukatani Kabupaten Bekasi - Akbar Anugerah Perkasa; Eka Wardhani; Athaya Zahrani Irmansyah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This research aims to identify the causes of flooding in Pasar Bancong, Sukatani Subdistrict, Bekasi Regency. The methods used were primary and secondary data collection, hydrological and hydraulic analysis, and drainage system design. The research results show that flooding in Pasar Bancong is caused by several factors, namely high rainfall intensity, low soil infiltration rate, inadequate capacity of the main channel, lower elevation of Pasar Bancong compared to the main road, and the presence of sediment and waste in the main channel. Two alternative treatments are proposed, namely sediment dredging and channel normalisation from upstream to downstream (Kali Gandu outfall). Changes in the dimensions of the drainage channel are planned to manage flooding in the design area. The conclusion of this study is that an assessment of the design area is required to identify problematic points in the drainage channel that require further treatment. The treatment that can be carried out is sediment dredging, normalisation and widening of the drainage channel dimensions.